KOMPARATIF TEKNIK DAN EKSPRESI DALAM SENI KRIYA - I Wayan Suardana (Imaji, 2006)
In modern system fine arts discourse these days, expression andtechnique region is always questioned to assign value whether/what themasterpiece can category as swan song or not. Expression always made byivorytower in creation of swan song of technique and always the attention cannotand considered to be skilled as supporter in course of the creation. Expression iseven also comprehended and careful shallow/ superficially where swan songwhich is not borne with emotional emotion it is not the expressive masterpieceendless. Understanding confusion bear all discourse of confused which to isolatein the end swan song which adiluhung placedly at region of swan song of underbecause assumed less be expressive. Regionas discourse problem of expressionand technique befall art kriya so that on the way nya artis tic [of] kriya havemultifarious to mention of manner that is crafting/ diligence art craft artistic ofartistic craft. This mention place art craft of at very region is corner. Very ironiconce where art craft which adiluhung category as art of second class of becauseits birth is assumed only need mere crafmanshif and without carryingexpression. Discourse mistake and have enter of at system discourse of fine artsby komfrehensif require to be straightened, so that domicile art become is equalto energy and material express different.Key word: kriya, crafmanshif, adiluhung